Quatre sonates pour le piano-forte composées par Louis van Beethoven. - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Mainz; Germany; Charles Zulehner, 2022)
Early edition of the Piano Sonatas opp. 10, nos. 1-3 and op. 7 published by Charles Zulehner in the Collection complete des oeuvres de musique pour le piano forte composées par Louis van Beethoven; Oeuvres de Louis van Beethoven Cahier VII, with plate numbers 95 (op. 10) and 94 (op. 7).